Assessment of the impact of implementing a personalized learning path for student athletes in the sport of skiing - Bryukhovskikh T.V.; Shubin D.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to evaluation of the success of the personalized educational path for student-athletes in the field of skiing. Methods and structure of the study. The educational research encompassed a group of 15 students-athletes pursuing their studies in the second year of the program 49.03.01 «Physical Education» at the university. For these students, an individualized learning path in the subject of Skiing was created in the form of an online course, which included essential theoretical content, including instructional videos, as well as specially designed tasks to assess their proficiency in the subject. The academic performance of the students during their study of the subject «Skiing» in the 2023-2024 academic year was analyzed as part of their individualized learning path. Additionally, upon completion of the subject, they were requested to fill out a survey in the form of a questionnaire to evaluate their satisfaction with the organization of their training. Results and conclusions. The findings of the research indicate that over 60% of student athletes have successfully completed the course in skiing and are content with the organization and content of the training program, which suggests the successful implementation of the individual educational path for students involved in sports.